The Use of a Role-Playing Learning Model for Teaching Speaking of the Eighth Grade Students - Wardani, Rizka Safira; Novita, Dian (Indonesian Journal Publisher, 2020)
This study aims to determine how teachers apply the Role-Playing learning model for teaching speaking of the eight grade students at SMP Muhammadiyah 8 Tanggulangin. In addition, the study also scrutinizes how students perceive if this method is applied in speaking class. Some of the eighth graders still do not master English. The situation is due to several factors from students, such as students' lack of confidence to speak English and lack of vocabulary knowledge, so students feel insecure when they want to speak English. Most of them need help speaking a foreign language since it differs from their everyday language. They need to be more confident in speaking English. In this study, the researchers used qualitative methods to describe the results of their research using observations and interviews. This research shows that teaching speaking with the role-playing model is very effective as a medium for teaching and learning English. Using the roleplaying model, students become more motivated and active in class.